Environmental Impact Assessment, Human Health and the Sustainable Development Goals - G. Gulis; N. Krishnankutty; E. R. Boess; E. R. Boess; I. Lyhne; L. Kørnøv (Frontiers Media S.A., 2022)
Objectives: Developmental processes influence the determinants of health and, consequently, human health. Yet, assessing human health impacts in impact assessment, with exception of health impact assessment, is still rather vague. Inclusion of Sustainable Development Goal indicators in environmental impact assessment (EIA) is an opportunity to enhance addressing human health in EIA practices.Methods: We reviewed a list of health-related targets and indicators for SDGs as defined by the Institute of Health Metrics and Evaluation (IHME) in Seattle, WA, United States with the aim of identifying those to be suggested as outcome indicators within EIA.Results: Among 42 health-related indicators, we identified 17 indicators which could be relevant for impact assessment procedures and categorized them into three groups: 1) direct health indicators (e.g., under five mortality). 2) complex indicators (e.g., cancer). 3) environmental determinant indicators (e.g., mean PM2.5).Conclusion: All 17 indicators can be employed to improve quantification assessing human health impacts and bring SDGs into EIA processes. Though our assessment has been conducted for Denmark and the set of suggested indicators could be different for contexts in other countries, the process of their identification can be generalized.